AKIBAT HUKUM PEMBATALAN PERJANJIAN SECARA SEPIHAK: Analisis Yuridis Putusan Mahkamah Agung tentang Hutang atau Prestasi - Hartanto, Kris (Al-Mazaahib: Jurnal Perbandingan Hukum, 2014)
In a reciprocal agreement, there is a right and an obligation on each partyto deal with the rights and obligations on the other, as well as relationshipin the law of agreement, whereby one party called the creditor and theother is called the debtor. Each party has the right and obligation bornof the legal relationship, the achievements and accomplishments counter.This paper analyzes the legal consequences of the agreement unilaterallycanceled as well as differences in the interpretation of the judge of theachievements in the two different cases that the Supreme Court decisionNo. 06 PK / N / 1999, concerning the bankruptcy case between Drs.Sani Hussein and Johan Subekti against PT. Modern Land RealityLtd. and Decision MA No. 08 K / N / 2004 on the bankruptcy casebetween PT. Prudential Life Assurance against Mr. Lee Boon Siong.In agreement, obligatoir such as buy-sell agreement there is always anobligation by one party is right and the obligation whose fulfillment canbe sued by the other party. Rights and obligations is exactly what thenis meant by achievement or debt that must be met by both the creditorand the debtor. Civil Code provide some remedy which can be selectedby the parties in the event of a breach of the contract of sale, namely:requesting execution of the agreement, demanding the cancellation ofthe agreement, and requested damages including lost profits due to loss.